Destruction, policy, and the evolving consequences of Washington, DC's 1968 Civil Disturbance - Leah Brooks; Jonathan Rose; Stan Veuger (Federal Reserve Bank of Chicago, 2022)
We study the aftermath of the 1968 Washington, DC civil disturbance to illuminate the mechanisms that drive urban redevelopment in the presence of low demand and racial tension. After establishing that civil disturbance property destruction was quasi-random within blocks, we show that destroyed lots were more likely, relative to other lots on the same block, to remain vacant for the next thirty years. We also show that destroyed lots have only recently converged in terms of structure value. Our theoretical framework suggests that the city sought to preclude for-profit land owners from leaving land vacant until demand conditions improved. As a result, the city purchased half of all properties in damaged neighborhoods and aimed to accelerate redevelopment, even if new structures were low value.
Keywords: R58; R11; N91; 330; Urban Redevelopment; Civil Disturbance; Option Value